Investment Treaty Disputes: Ideological Fault Lines and an Evolving Zeitgeist - HSU, Locknie (Institutional Knowledge at Singapore Management University, 2011)
The zeitgeist of the 21st century in the field of investment treaty arbitrations comprises a rise in the number of such arbitrations and accompanying observations on the unwieldy jurisprudential effects of such a rise. The international investment arbitration community is alive with discussion over these effects, which discussion includes an examination of the value of prior awards as precedents.' The existing regime based on treaty interpretation clearly provides no formal system of precedent and the 'players' (read: arbitrators) change from dispute to dispute as investment arbitration tribunals do not fall within a single, neat judicial hierarchical system. With the number of investor-State disputes and investment arbitration awards increasing, relatively new questions (and concerns) over these effects have therefore arisen.